Design and Implementation of High Frequency Broadband Gbit/s System Based on MIMO-OFDM - Junyu Peng; Sunzeng Cai; Zhenghang Zhu; Jing Xu; Ting Zhou (Dianxin kexue)
Spectrum bands below 6 GHz have been crowded currently,but demand for high speed wireless communication in low speed environment is growing.Research and development of high-frequency wireless communication system is an important way to alleviate this problem.System structure for high frequency broadband communication was proposed.Physical layer key algorithm such as synchronization,channel estimation and MIMO detection was described briefly.The high frequency broadband Gbit/s system based on MIMO-OFDM was implemented on FPGA based hardware platform.Bandwidth and data rate of the system was tested in indoor environment.Test result shows that performance of the system conforms to design requirements.